Efficacy of immune checkpoint inhibitors in older adults with advanced stage cancers: A meta-analysis. Issue 3 (April 2020) - Kasherman, Lawrence; Siu, Derrick Ho Wai; Lee, Kirsty Wai Chung; Lord, Sally; Marschner, Ian; Lewis, Craig R.; Friedlander, Michael; Lee, Chee Khoon
Abstract: Objectives: There is uncertainty whether older patients derive a similar benefit from immune checkpoint inhibitors (ICI) as younger patients. We performed a meta-analysis of ICI trials in advanced cancers to better estimate treatment benefit in the older population. Materials and Methods: We performed an electronic search for randomized trials of ICI, either as monotherapy or in combination with other agents. Hazard ratios (HR) for subgroups defined by different age cut-offs were extracted. Pooled overall survival (OS) treatment estimates were calculated using the inverse variance weighted method. Results: In nineteen trials comparing ICI monotherapy versus non-ICI treatment, there was no significant treatment–age interaction (age ≥ 65 years: N  = 6064, HR 0.73; age < 65 years: N  = 7250, HR 0.79; P-interaction  = 0.27). Findings were similar at older age cut-offs of 70 years (age ≥ 70 years: N  = 433, HR = 0.93; age < 70 years: N  = 169, HR = 0.95; P-interaction  = 0.91) and 75 years (age ≥ 75 years: N  = 139, HR = 0.75; age < 75 years: N  = 1133, HR = 0.61; P-interaction  = 0.72) respectively, and for trials of ICI combination therapy. Conclusion: ICI therapy improves OS in both younger and older patients with advanced cancers, and the magnitude of improvement does not depend on age. Patient selection for ICI therapy should be done based on performance status and adequate organ function independently of age.